Dream recall after multiple sleep latency test naps with and without REM sleep - Olbrich, Kate Isobel; Schredl, Michael (International journal of dream research, 2019)
The current paper aimed to look into whether Rapid Eye movement (REM) sleep and narcolepsy would have an influence on dream recall frequency after a nap within the Multiple Sleep Latency Test (MSLT) procedure. Overall, 146 patients with a large variety of diagnoses were included. Patients completed a scale measuring dream recall frequency prior to the study and after every MSLT nap an item whether they could recall a dream or not. The findings indicate that REM naps yielded higher dream recall rates than naps without REM and that narcolepsy patients reported higher dream recall than patients with other diagnoses. The results supported the functional state-shift model of dream recall but also provided evidence that models that include physiological as well as psychological variables are most promising for explaining intra-individual and inter-individual differences in dream recall.